FRER mechanism based on frame preservation caching in time-sensitive networking - CAI Yueping; HU Shaoliu; HAN Xiao (Tongxin xuebao)
An improved FRER mechanism based on frame preservation caching at intersecting node (FRER-FPCIN) was proposed to solve the frame disorder problems, which resulted in the cache overflow and frame discarding. The disordered frames were resorted at the intersection nodes through frame arrival events and timer timeout events to ensure orderly forwarding of frames. The design of cache size and timer was also analyzed. Simulation results show that the proposed mechanism effectively reduces the frame loss rate, average frame delay and jitter compared with traditional frame ordering mechanisms.